Impact of Growth Rate on the Welfare of Broilers - Anja B. Riber; Kaitlin E. Wurtz (Animals)
Selection for the more efficient production of broilers has resulted in rapid growth rates. The aim was to review the existing knowledge on the effect of growth rate on broiler welfare. Genotypes with faster growth rates consistently demonstrate poorer gait scores and increased prevalence of disorders affecting their legs than slower-growing genotypes. Reduced mobility places faster-growing broilers at an increased risk of developing contact dermatitis, as they spend increased durations sitting in contact with litter. Poor walking ability, heavy body weights, and conformational differences such as proportionally larger breast muscle in genotypes with faster growth can impact a bird’s ability to walk and navigate the environment, making it difficult to access resources and express natural behaviors. Faster growth has also been associated with poor cardiovascular health, increased susceptibility to heat stress, increased prevalence of mortality, ascites, as well as multiple breast muscle myopathies. Feed restriction, a practice associated with hunger and frustration, may be used to control the growth of broiler breeders, with birds having higher growth potential typically experiencing higher restriction levels. Overall, there is strong evidence that fast growth rates negatively impact welfare, and that slower-growing genotypes show significantly improved welfare. Furthermore, some evidence suggests that even minor reductions in growth rate can lead to welfare improvements.